Evaluation of the effectiveness of new mixed ligand complexes against the vector of Dengue fever Aedes aegypti (Diptera; Culicidae) - Al–Selwi, Nedhal Abdulmawla; Al–Azab, Abbas Mohamed; Jamil, Yasmin Mosa’d Saeed; Al–Azab, Fathi Mohamed; Al–Ryami, Anwar Mohamed (Eclética Química, 2024)
Chloroquine phosphate with ibuprofen and sulphamethoxazole were used as mixed ligands with Ni(II), Co(II), Cu(II), and Zn(II) to prepare new transition metal complexes. Metal analysis, IR, and X-ray diffraction (XRD) spectrum analyzes were used to describe them, with some modifications to the World Health Organization (WHO) standard susceptibility test under laboratory conditions. The biological effects of ligands and new complexes against Aedes aegypti mosquito larvae were evaluated at various concentrations. To assess larvicidal efficacy, late third or early fourth instar larvae were exposed to multiple concentrations of the examined compounds, ranging from 50 to 1000 ppm. Cu(II) complexes revealed significant high activity (LC50 = 100 ppm against Ae. Aegypti was compared with the rest of the metal complexes. On the other hand, the Co(II) complex showed no activity against Ae. aegypti. These mixed ligand complexes seemed to be an alternative method for manufactured insecticides to control larvae of this medically important mosquito vector Ae. aegypti. Further research on other metal complex compounds responsible for larvicidal efficacy will be required.